Manual of procedures for trainers in sustainable tourism - Diaz Quintero, Gisela (ACS Port of SpainTT)
Targets trainers, who will be responsible for implementing the process in countries. Presents the steps to be taken toward organising tasks. Provides the information that must be compiled when performing the diagnosis of the territory; suggests ways on how to use it to better control performance; suggests how to define indicators and evaluate them; in addition indcates the procedure to be followed for the monitoring and self-evaluation of the sustainability of the destination.